The evolution of motifs on traditional malay wood carving in the islamic era - Fadzillah binti A. Rahim
Traditional Malay wood carving constitutes an essential art form that projects the rich tradition of the Malay culture. The dwindling appearance of traditional Malay houses means that the art of crafting wood carved panels is in decline. Inside the Malay homes, the traditional Malay biscuit moulds and coconut graters made from wood and decorated with beautiful engravings have been completely replaced by plastic ones. As Malaysia is rapidly modernizing and industrializing, the slow disappearance of traditional ornaments and their intricate and meaningful motifs has largely gone unnoticed. These wood carved artefacts from the past display typical motifs that were being transferred from one tradition to the other. After the advent of Islam, its religious teachings impacted on the motifs, which changed in their style and shape. The first objective of this study is to identify the traditional Malay wood carving motifs in the 19th and 20th century. It also examines the style of the motifs on the traditional Malay wood carvings produced during this period. The third objective is to examine the evolution of motifs on traditional Malay wood carving in the 19th and 20th century. The aim is to investigate the evolution of motifs as well as styles that dictates these motifs. The study employed the formalistic analysis method and identifies the evolution and style of motifs found on the selected wood carvings. The wood carvings from Kelantan and Terengganu were obtained from the International Art Museum Malaysia, Muzium Seni Asia, Muzium Terengganu and Akademi Nik Rashiddin. Apart from the field study and formalistic analysis method, interviews were conducted with academicians, curators, and wood carvers. The researcher interviewed the founder of the Akademi Nik Rashiddin, the senior assistant of the Muzium Terengganu, the senior curator of the Muzium Seni Asia, the Head of the Department Wood Craft of the Institut Kraf Negara, and the operation manager of Inakraf Wood Carving who is also a renowned wood carver. This study goes beyond the usual scope of studying architectural panels by including daily domestic items, boat accessories, traditional games, religious products, tools, traditional music, weapons, and furniture. A total of 74 artefacts dating from the 19th and 20th century was analysed in order to identify the motifs and examine their styles. The results reveal that floral, geometrical and Arabic calligraphy governs the selected wood carvings and that the dominating motif is floral. The findings of this study show evidence of evolution in the depiction of various motifs on the traditional Malay wood carving even though these changes are very subtle. Through analysis of the artefacts from this period it is found that the depiction of the motifs was highly stylized in order to avoid a direct representation of nature as prohibited in Islamic art. This study suggests that all the wood carving motifs produced in the 19th and 20th century should be properly recorded and safely stored in a digital database format before their complete disappearance. The motifs on the wood carvings that are being produced today tend to be increasingly modern, while the traditional motifs are being discarded. Once these traditional motifs have been stored and preserved, future artisans and craftsmen will be able to rediscover them and apply them on any structure or surface for embellishment. The traditional Malay motifs are part and parcel of the traditional Malay heritage and deserve to be preserved.